Germinação de sementes in vitro e desenvolvimento de plantas ex vitro de algodãozinho-do-campo - Inácio, Marielle Cascaes [UNESP]; Bertoni, Bianca Waléria; de Castro França, Suzelei; Pereira, Ana Maria Soares [UNESP] (FapUNIFESP (SciELO), 2010)
This study was designed to conduct experiments with germination and dormancy breaking in in vitro seeds of Cochlospermum regium in vitro and evaluate the development of plants ex vitro for this species. For the sterilization of seeds introduced in vitro, were used benlate, calcium hypochlorite and sulfuric acid. The break dormancy was realized with seeds immersed in sulfuric acid for different periods. To check the influence of seed size on germination, they were lassified as large (A=34.08mm2), medium (A=27.74mm2) and small (A=17.99mm2). For the development of ex vitro plants were used sand substrate or Cerrado soil + manure. Efficient sterilization of seeds was achieved with the use of sulfuric acid. The immersion for 146 and 144 minutes, to break dormancy, showed higher germination rate and germination speed of 63% and 0,78 respectively - with no contamination. Larger seeds germinated faster (0.61) than smaller ones. Though ex vitro development of plants cultured in both substrates was similar, plantlets cultured in soil + manure were more vigorous.
In vitro seeds germination and ex vitro plants development of algodãozinho-do-campo
Keywords: Cerrado; Cochlospermaceae; Cochlospermum regium; Dormancy; Propagation